Clinical impact and course of major bleeding with rivaroxaban and vitamin K antagonists. (22nd August 2015) - Eerenberg, E. S.; Middeldorp, S.; Levi, M.; Lensing, A. W.; Büller, H. R.
Summary Background Rivaroxaban is a new oral anticoagulant (NOAC) that can be prescribed in a fixed dose, making regular monitoring and dose adjustments unnecessary. It has been proven to be safe and effective in comparison with enoxaparin/vitamin K antagonists (LMWH/VKA) for the (extended) treatment of venous thromboembolism in the EINSTEIN studies. Nevertheless, there is a need for information regarding the clinical impact of (major) bleeding events with NOACs such as rivaroxaban. Objectives A post‐hoc analysis was performed to compare the severity of clinical presentation and subsequent clinical course of major bleeding with rivaroxaban vs. LMWH/VKA. Methods Two investigators performed a blinded classification of major bleeding using a priori defined criteria. During the EINSTEIN studies, data concerning the clinical course and measures applied were prospectively collected for each major bleed. Results Treatment with LMWH/VKA caused more major bleeding events (1.7%) than rivaroxaban (1.0%; hazard ratio, 0.54; 95% confidence interval [CI], 0.37–0.79). Major bleeding events during rivaroxaban therapy had a milder presentation (23% were adjudicated to the worst categories vs. 38% for LMWH/VKA; hazard ratio or HR, 0.35; 95% CI, 0.17–0.74; P = 0.0062). The clinical course was severe in 25% of all major bleeding events associated with rivaroxaban, compared with 33% of LMWH/VKA‐associated bleeds (HR, 0.46; 95% CI, 0.22–0.96; P = 0.040). Conclusions Rivaroxaban‐associated major bleeding events occurred less frequently, had a milder presentation and appeared to take a less severe clinical course compared with major bleeding with LMWH/VKA.